1999
DOI: 10.1038/sj.leu.2401420
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin structure and transcriptional regulation of the stem cell leukaemia (SCL) gene in mast cells

Abstract: The stem cell leukaemia (SCL) gene is a member of the basic helix-loop-helix family of transcription factors and is essential for the development of all haematopoietic lineages. SCL is expressed in pluripotent haematopoietic stem cells and also following commitment to the erythroid, mast and megakaryocytic lineages. The mechanisms responsible for this pattern of expression are poorly understood, but are likely to illuminate the molecular basis for stem cell development and lineage commitment. Here we present t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…Three regions of accessible chromatin were identified ( Fig. 3B; data not shown), all of which coincided with the regions previously mapped in murine hematopoietic cell lines (24). The positions of the accessible restriction endonuclease sites were identified in the mouse sequence and compared to a human/ mouse homology profile.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Three regions of accessible chromatin were identified ( Fig. 3B; data not shown), all of which coincided with the regions previously mapped in murine hematopoietic cell lines (24). The positions of the accessible restriction endonuclease sites were identified in the mouse sequence and compared to a human/ mouse homology profile.…”
Section: Resultssupporting
confidence: 75%
“…However, a 6.3-kb fragment from the 5Ј region of the mouse scl gene directed expression to the vast majority of embryonic endothelial cells, together with rare round cells in the fetal liver (62). Moreover, the same fragment had also been shown to contain three regions of open chromatin in murine myeloid cell lines (24,32), suggesting that the rare round fetal liver cells may be of hematopoietic origin. We therefore investigated whether the scl 5Ј region contained an enhancer that might ensure scl expression during hematopoietic differentiation of scl ⌬19/⌬19 ES cells.…”
Section: Resultsmentioning
confidence: 99%
“…Within this well-characterized region, two novel DNaseI hypersensitive sites were identified as significantly enriched (+29 and +32) and investigated in functional assays. These sites are outside the region previously mapped with Southern blotting, although restriction enzyme ac- (Fordham et al 1999;Göttgens et al 1997Göttgens et al , 2004Sinclair et al 1999) Promoter 1a Promoter 1a 113402105-113402405 Yes Yes No Yes (Aplan et al 1990;Bockamp et al 1995Bockamp et al , 1997Bockamp et al , 1998Fordham et al 1999;Göttgens et al 1997Göttgens et al , 2001Sinclair et al 1999) Promoter 1b Promoter 1b 113402565-113402725 Yes Yes No Yes (Bockamp et al 1995(Bockamp et al , 1998Fordham et al 1999;Göttgens et al 1997Göttgens et al , 2001Sinclair et al 1999) cessibility mapping around the Pdzk1ip1 gene in 416B cells has now identified both regions as hypersensitive using conventional Southern blotting approaches (data not shown). Consistent with its location immediately upstream of Pdzk1ip1 exon 1, the +32 element functioned as a promoter in transient and stable reporter assays (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Both human and mouse SCL are transcribed from two lineage-specific promoters (20)(21)(22)(23)(24). In addition, a panel of DNase I hypersensitive sites associated with enhancer or silencer activity have been identified within the murine SCL locus (25,26). Studies using transgenic mice have subsequently defined a 30-kb region containing five distinct murine enhancers that are capable of directing reporter gene expression to hemopoietic progenitor cells, endothelium, and specific regions of the brain and spinal cord (6,27,28).…”
mentioning
confidence: 99%